Efektivitas Model Pembelajaran Kooperatif Tipe Scramble Pada Materi Bangun Ruang Terhadap Hasil Belajar Matematika Siswa Mts Fie Sabilil Muttaqien Tempurejo: Novia Putri Pratiwi*, Anwas Mashuri, Amiratih Siti Aisyah - Novia Putri Pratiwi; Anwas Mashuri; Amiratih Siti Aisyah (Samudra Publisher, 2024)
This research seeks to identify learning models that influence students' mathematics learning outcomes. Students at MTs FSM Tempurejo have low learning outcomes, because learning is still centered on the teacher. One learning model that can be used is the Scramble Type Cooperative Learning model. This quantitative research uses Post Test Only Control Design, with two samples selected using Cluster Random Sampling, one class as the experimental class and one class as the control class, and using one class, namely class IX A as the test class. The samples are normally distributed and homogeneous. Data analysis uses t test. The Scramble Type Cooperative Learning Model produced an average of 70.76, while direct learning produced an average of 44.36. Students who were taught using the Scramble Type Cooperative Learning Model obtained a better average and mastery compared to students who were taught using the Scramble Type Cooperative Learning Model. directly, as calculated by this research, t-count > t-table with a t-count=7.016 and a t-table value=2.045.